Studying the Role of Haptic Feedback on Virtual Embodiment in a Drawing Task - Richard, Grégoire; Pietrzak, Thomas; Argelaguet, Ferran; Lécuyer, Anatole; Casiez, Géry (Frontiers in Virtual Reality, 2021)
The role of haptic feedback on virtual embodiment is investigated in this paper in a context of active and fine manipulation. In particular, we explore which haptic cue, with varying ecological validity, has more influence on virtual embodiment. We conducted a within-subject experiment with 24 participants and compared self-reported embodiment over a humanoid avatar during a coloring task under three conditions: force-feedback, vibrotactile feedback, no haptic feedback. In the experiment, force-feedback was more ecological as it matched reality more closely, while vibrotactile feedback was more symbolic. Taken together, our results show significant superiority of force-feedback over no haptic feedback regarding embodiment, and significant superiority of force-feedback over the other two conditions regarding subjective performance. Those results suggest that a more ecological feedback is better suited to elicit embodiment during fine manipulation tasks.